Anger Elicitation in Tonga and Germany: The Impact of Culture on Cognitive Determinants of Emotions - Bender, Andrea; Spada, Hans; Rothe, Annelie; Traber, Simone; Rauss, Karsten (Frontiers in Psychology, 2012)
The cognitive appraisal of an event is crucial for the elicitation and differentiation of emotions, and causal attributions are an integral part of this process. In an interdisciplinary project comparing Tonga and Germany, we examined how cultural differences in attribution tendencies affect emotion assessment and elicitation. Data on appraising causality and responsibility and on emotional responses were collected through questionnaires based on experimentally designed vignettes, and were related to culture-specific values, norms, and the prevailing self-concept. The experimental data support our hypothesis that—driven by culturally defined self-concepts and corresponding attribution tendencies—members of the two cultures cognitively appraise events in diverging manners and consequently differ in their emotional responses. Ascription of responsibility to self and/or circumstances, in line with a more interdependent self-concept, co-varies with higher ratings of shame, guilt and sadness, whereas ascription of responsibility to others, in line with a less interdependent self-concept, co-varies with higher ratings of anger. These findings support the universal contingency hypothesis and help to explain cultural differences in this domain on a fine-grained level.